(untitled) (AYUSHDHARA, 2016)
The life of every individual starts with the healing of the wound of the cut umbilical cord. So, treatment for healing of this wound is of prime importance. While explaining the scope of Shalya Tantra. Even though healing of Vrana is a natural process of the body, the Vrana should be protected from Dosha Dushti and from various micro organisms, which may afflict the Vrana and delay the normal healing process. So, for the early and uncomplicated healing of Vrana, treatment is necessary. In healing of Vrana, local treatment is also important along with oral medications. Dushta Vrana is a long standing ulcer with profuse discharge and slough, where clearing slough and enabling drug to reach the healthy tissue is more important. Slough can be cleared by using surgical instruments or oxidizing agents where healthy granulation tissues are damaged. In recent years various efforts were made in the field of wound healing, especially as local treatments but healing remains the prime objective of the physicians. Though the herbal drugs are prescribed with high appreciation for healing purpose but it needs scientific evaluation with proper study design. Keeping all these things in view, drugs like Sharpumkha and Madhu has been selected after reviewing the literature. This study is designed to conduct an experimental as well as a clinical study thoroughly. The study is entirely based on clinical observation and assessment of selected 60 patients attending OPD/IPD were selected randomly and subjected to clinical trial. Duration of study for 12 days administered with Madhuyukta Sharpumkhamoola lepa and Betadine ointment.